Curvature-induced electronic tuning of molecular catalysts for CO2 reduction. Issue 7 (3rd February 2021) - Tian, Pengfei; Zhang, Bo; Chen, Jiacheng; Zhang, Jing; Huang, Libei; Ye, Ruquan; Bao, Bo; Zhu, Minghui
Abstract : A curvature-induced electronic tuning strategy of molecular catalysts for CO2 reduction is proposed. Abstract : Molecular complexes such as phthalocyanines and porphyrins are attractive due to their outstanding performance towards CO2 -to-CO conversion. In this work, immobilized cobalt phthalocyanine (CoPc) is prepared using a CVD-type procedure. Our theoretical calculations suggest that depositing CoPc onto a highly curved substrate leads to structural deformation and electronic tuning that can decrease the activation barrier of CO2 . Consistent with theoretical predictions, the intrinsic activity of CoPc supported on SWCNTs is improved by two folds compared to that on less-curved surfaces such as reduced graphene oxide (rGO) or multi-wall carbon nanotubes (MWCNTs). The catalyst exhibits a high Faradaic efficiency for CO of 80% at a low overpotential of 240 mV. At a higher overpotential of 490 mV, a TOF of 26.0 s −1 and a TON of ca. 90 000 are obtained with a near-unity Faradaic efficiency.